2017
DOI: 10.3906/elk-1605-40
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for minimizing torque ripple in a BLDC motor drive with a front end IDO dc-dc converter

Abstract: This paper proposes a front end integrated dual output (IDO) dc-dc converter for commutation torque ripple reduction in a permanent magnet brushless DC (BLDC) motor drive. The current ripple owed to the inductance and resistance of the motor during commutation instant results in torque ripple. In this work the dc link voltage of the converter is varied at commutation instants to minimize current ripple and hence torque ripple. The wider output range and faster response of the IDO converter make it a suitable c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…(11) and (13), it is theoretically seen that if the input voltage of the inverter is equal to four times of the back EMF at the commutation intervals, torque ripples can be completely zero. This equalization was carried out using different DC-DC converters [6,[17][18][19]. In most of the studies, it was assumed that the rotor speed was constant in the commutation intervals.…”
Section: Analysis Of Speed Fluctuation In Brushless DC Motormentioning
confidence: 99%
See 1 more Smart Citation
“…(11) and (13), it is theoretically seen that if the input voltage of the inverter is equal to four times of the back EMF at the commutation intervals, torque ripples can be completely zero. This equalization was carried out using different DC-DC converters [6,[17][18][19]. In most of the studies, it was assumed that the rotor speed was constant in the commutation intervals.…”
Section: Analysis Of Speed Fluctuation In Brushless DC Motormentioning
confidence: 99%
“…This case, is shown in Figs. 15,16,17, respectively. According to the simulation results it was observed that the disturbances occurring in the phase currents affect the rotor speed directly.…”
Section: Proposed Control Strategymentioning
confidence: 99%
“…Multilevel inverters and modified converters topologies have also gained much attention for current ripple minimization. This is due to their advantages, compared to conventional topologies, such as less switching voltage stress and lower switching losses [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The input signals of the controller were back-emf and the change of the back-emf during the commutation period. In [11], a developed integrated dual-output converter including switch selector has been proposed for reducing ripples in torque during a commutation period. Good performance has been achieved compared with a conventional converter.…”
Section: Introductionmentioning
confidence: 99%